لجنة بحث المسائل الدينية لجمعية نهضة العلماء بإندونيسيا: دراسة نقدية على المقررات الفقهية (JOURNAL OF INDONESIAN ISLAM, 2007)
This article seeks to shed light on the decrees released by Lajnah Baḥth al-Masā’il Nahdlatul Ulama (NU) on matters pertaining to religious disputes (masā’il al-fiqhiyyah). It focuses on two main themes; (1) the definition of what books are categorized as “al-Kutub al-Mu‘tabarah” and (2) the methodological approach used by the Lajnah in the process of deliberation. The assumption developed within this article is that what makes the books fall into the category of “al-Kutub al-Mu‘tabarah” are only those books that employ one of the four school of thought in fiqh. In addition, the methodological approach used in the Lajnah follows the following three patterns: (1) al-Ṭarīqah al-qawliyyah (direct reference to those mu‘tabarah books), (2) al-Ṭarīqah al-ilḥāqiyyah (analogy between old and new problems as mentioned within those mu‘tabarah books), (3) al-Ṭarīqah al-manhajiyyah (following the methods of four madhhab imams).